Using e-portfolios to facilitate reflection: Insights from an activity theoretical analysis. (October 2019) - Chye, Stefanie; Zhou, Mingming; Koh, Caroline; Liu, Woon Chia
Highlights: The utility of the e-portfolio as a reflection tool has been widely endorsed in theory. Conflicting results have been yielded when examined from student teachers' perspectives. Research in this area lacks a systematic theoretical framework. Cultural-Historical Activity Theory is proposed as a unifying framework. A sample analysis using CHAT suggests that CHAT is a potentially useful analytical tool.